2016
DOI: 10.3389/fphar.2016.00221
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids As Potential Treatment for Chemotherapy-Induced Nausea and Vomiting

Abstract: Despite the advent of classic anti-emetics, chemotherapy-induced nausea is still problematic, with vomiting being somewhat better managed in the clinic. If post-treatment nausea and vomiting are not properly controlled, anticipatory nausea—a conditioned response to the contextual cues associated with illness-inducing chemotherapy—can develop. Once it develops, anticipatory nausea is refractive to current anti-emetics, highlighting the need for alternative treatment options. One of the first documented medicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 95 publications
(130 reference statements)
0
32
1
Order By: Relevance
“…In regard to cannabinoid-elicited nausea, Hempel et al (2017) showed that THC was more potent and efficacious in female rats compared to males in decreasing saccharin consumption in a conditioned taste aversion procedure, suggesting that females are more sensitive than males to the aversive effects of THC, or females were better than males at learning the drug-taste association (which the authors concluded may be the case). Interestingly, considerable animal research suggests that cannabinoid treatment could be useful for alleviating chemotherapy-induced nausea and vomiting (Rock and Parker, 2016). Given that women may be more susceptible than men to chemotherapy-induced nausea (Hilarius et al, 2012), sex comparisons of cannabinoids' anti-nausea and anti-emetic effects in animal studies (and analysis of results by sex in human studies) are warranted.…”
Section: Potential Therapeutic Effects Of Cannabis and Cannabinoidsmentioning
confidence: 99%
“…In regard to cannabinoid-elicited nausea, Hempel et al (2017) showed that THC was more potent and efficacious in female rats compared to males in decreasing saccharin consumption in a conditioned taste aversion procedure, suggesting that females are more sensitive than males to the aversive effects of THC, or females were better than males at learning the drug-taste association (which the authors concluded may be the case). Interestingly, considerable animal research suggests that cannabinoid treatment could be useful for alleviating chemotherapy-induced nausea and vomiting (Rock and Parker, 2016). Given that women may be more susceptible than men to chemotherapy-induced nausea (Hilarius et al, 2012), sex comparisons of cannabinoids' anti-nausea and anti-emetic effects in animal studies (and analysis of results by sex in human studies) are warranted.…”
Section: Potential Therapeutic Effects Of Cannabis and Cannabinoidsmentioning
confidence: 99%
“…THC has many beneficial activities, for example, antiemetic and analgesic, and could be used for the treatment of anorexia, glaucoma, chemotherapy-induced emesis, and several types of cancer. However, its potent psychoactivity prevents or limits its medical use [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. Another important promising phytocannabinoid is cannabidiol (CBD).…”
Section: Medicinal Properties Of Cannabinoidsmentioning
confidence: 99%
“…36 ). Both nabilone and dronabinol are available in capsules and are used to treat chemotherapy-induced nausea and vomiting, particularly in oncologic patients who have not responded to standard means for control of these conditions 37 . Dronabinol is also used to treat anorexia associated with AIDS (ref.…”
Section: Approved Cannabis-based Productsmentioning
confidence: 99%
“…38 ). Dronabinol is synthetic THC, nabilone is synthetic THC analogue; each of these substances has partially agonistic effect at the cannabinoid CB 1 and cannabinoid CB 2 receptors 37 .…”
Section: Approved Cannabis-based Productsmentioning
confidence: 99%